Stress hormones and posttraumatic stress symptoms following paediatric critical illness: an exploratory study. - Als, Lorraine; Picouto, Maria; O'Donnell, Kieran; Nadel, Simon; Cooper, Mehrengise; Pierce, Christine; Kramer, Tami; Glover, Vivette; Garralda, M. (European Child & Adolescent Psychiatry, 2017)
In this exploratory case-control study, we investigated basal cortisol regulation in 5-16-year-old children, 3-6 months following PICU (paediatric intensive care) admission. This was nested within a study of child psychological and cognitive function; 47 children were assessed alongside 56 healthy controls. Saliva samples were collected three times per day (immediately after waking, waking +30 min, and waking +12 h) over two consecutive weekdays. In addition, data on posttraumatic stress symptoms were ascertained from 33 PICU admitted children using the Impact of Events Scale-8 (IES-8). Primary analysis revealed no significant differences in basal cortisol concentrations between PICU discharged children and healthy controls ( p > 0.05). Secondary analysis in the PICU group identified a significant positive association between posttraumatic stress symptoms and evening (waking +12 h) cortisol concentrations ( p = 0.004). However, when subject to multivariate analysis, evening cortisol was a modest independent predictor of IES-8 scores, relative to the presence of septic illness and poor pre-morbid health. We conclude that paediatric critical illness does not appear to result in marked perturbations to basal cortisol at 3-6 month following discharge. There was evidence of a link between evening cortisol and symptoms of PTSD, but this was not a robust effect and requires further elucidation.